When Competition Breaks the Rules: Feeding Frenzy as a Trigger for Unexpected Fatal Shark Predation Bites on a Human Sea‐User by Non Traumatogenic Carcharinids in the Oriental Mediterranean - Clua, Eric E. G.; Parton, Kristian. J. (Ethology, 2025)
ABSTRACT The fatal shark attack on a male tourist in Hadera (Oriental Mediterranean coast) in 2025 involved several Dusky sharks (Carcharhinus obscurus), a species not considered to be traumatogenic to humans. Artificial provisioning in the area has resulted in habituation with behaviors including begging, potentially resulting in a bold shark displaying a first reflex/clumsiness bite targeting the camera held by the snorkeler, unintentionally wounding him. The sound and olfactory stimuli have likely triggered a feeding frenzy leading to multiple sharks engaging in predation bites. In this case study, extreme competition between individuals has probably overridden the non‐instinctive prey nature of the human victim. Feeding frenzy may lead non‐traumatogenic shark species to predate a human, despite this not being an instinctive prey item. As a first step, an initial non‐predatory bite (not targetting the human as a prey) can trigger multiple feeding stimuli (mainly sounds and blood smelling) attracting sharks in the area. As a second step, competition results in other sharks displaying multiple predation bites ending in a fatality.